Effect of different nutrient management practices on productivity, soil physical and physico-chemical properties in chickpea (Cicer arietinum L.) - Valluri Sandhya Rani; A. Malliswara Reddy; P. V. Ramesh Babu; P. V. Geetha Sireesha; M. Srinivasa Reddy (Annals of Agricultural Research, 2023)
A field experiment was conducted to study the effect of rhizobium and seaweed extract on soil parameters of chickpea (Cicer arietinum L.) under scarce rainfall zone of Andhra Pradesh on sandy loam soils of Mahanandi campus of Acharya N. G. Ranga Agricultural University during rabi, 2022-2023. The experiment was laid out in randomized block design with seven treatments and three replications. The results revealed that, soil bulk density was found non-significant, whereas porosity and water holding capacity of soil was significantly higher with combined application of rhizobium inoculation with seaweed extract along with 75% recommended dose of fertilizers. Soil physico-chemical properties viz., soil pH, electrical conductivity (EC) and organic carbon (OC) were found non-significant with different nutrient management practices. Post-harvest soil macro nutrients (N,P,K) and micronutrients (Zn, Fe, Cu, Mn), seed and stover yield were significantly higher with combined application of 75 % RDF + seed treatment with rhizobium + seed soaking with 0.1 % seaweed extract + foliar application of 0.3 % seaweed extract at 25 DAS. The integrated nutrient management practices have improved the soil physical, physico-chemical and chemical properties in chickpea cultivation under scarce rainfall zone of Andhra Pradesh.